Copper‐Catalyzed Difluoroalkylation‐Thiolation of Alkenes Promoted by Na2S2O5. Issue 12 (22nd March 2021) - Gao, Bao; Ni, Yingjie; Liu, Xiaojun; Jiang, Tao; Yan, Qian; Yang, Ruiting; Zhang, Xiuli
Abstract: A novel and convenient protocol for the difluoroalkylation‐thiolation of alkenes catalyzed by Cu/Na2 S2 O5 system has been developed. This reaction was carried out using readily available starting materials under mild conditions, wherein the C−C and C−S bonds simultaneously were constructed smoothly. The reaction features broad substrate scope of alkenes and disulfides, good functional group tolerance, and good to excellent yields with high selectivity. Abstract : We report an efficient protocol for the difluoroalkylation‐thiolation of alkenes catalyzed by Cu/Na2 S2 O5 system with disulfides as a sulfur source. This reaction allows a variety of alkenes and disulfides, wherein the new C−C and C−S bonds were simultaneously constructed.